2015
DOI: 10.1021/jp5094349
|View full text |Cite
|
Sign up to set email alerts
|

Ion Transport in Na2M2TeO6: Insights from Molecular Dynamics Simulation

Abstract: An interatomic potential is proposed for the recently discovered family of superionic solids of the formula Na2M2TeO6, where M = Ni, Zn, Co, or Mg. Molecular dynamics simulations demonstrating the quality of the potential in reproducing various structural and transport properties of this promising class of materials is presented. The study provides fresh insights on the microscopic energetics and Na+ migration pathways. Strong ion–ion correlations, resulting in a highly cooperative conduction mechanism, emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 50 publications
(72 reference statements)
4
36
0
Order By: Relevance
“…Thereafter Na–Na and Na–O potentials were fine‐tuned to reproduce the conductivity and overall structure–dynamic properties agreeing with experimental data. The initial studies showed that ion–ion correlation effects, indicating a cooperative conduction mechanism, and a strongly disordered sublattice for the Na ions were key to fast ion transport, similarly to what had previously been shown for both Nasicon as well as β‐alumina. This ion–ion correlation was later examined in more detail for Na 2 Ni 2 TeO 6 by systematically changing the Na‐occupancy in the conduction layers, resulting in a conduction variation by an order of magnitude, maximum at 20% Na deficiency.…”
Section: Ceramic Glassy and Solid‐state Ionic Materialssupporting
confidence: 60%
See 1 more Smart Citation
“…Thereafter Na–Na and Na–O potentials were fine‐tuned to reproduce the conductivity and overall structure–dynamic properties agreeing with experimental data. The initial studies showed that ion–ion correlation effects, indicating a cooperative conduction mechanism, and a strongly disordered sublattice for the Na ions were key to fast ion transport, similarly to what had previously been shown for both Nasicon as well as β‐alumina. This ion–ion correlation was later examined in more detail for Na 2 Ni 2 TeO 6 by systematically changing the Na‐occupancy in the conduction layers, resulting in a conduction variation by an order of magnitude, maximum at 20% Na deficiency.…”
Section: Ceramic Glassy and Solid‐state Ionic Materialssupporting
confidence: 60%
“…A novel class of Na + conductors is Na 2 M 2 TeO 6 , where M = Ni, Zn, Co, or Mg, built from edge‐sharing M–O and T–O octahedral layers, with Na + in the interlayer, result in conductivities similar to β‐alumina: 0.11 S cm −1 at 573 K . This was explored by classic MD simulations, using a FF constructed by fitting parameters in short‐range MD simulations until the crystallographic structure was reproduced. Thereafter Na–Na and Na–O potentials were fine‐tuned to reproduce the conductivity and overall structure–dynamic properties agreeing with experimental data.…”
Section: Ceramic Glassy and Solid‐state Ionic Materialsmentioning
confidence: 99%
“…In this context, modeling the potential parameter to perform CMD would play a major role in opening up various theoretical studies to understand fundamentals of ion-hopping mechanisms. The potential of CMD has already been proven in systems such as AgI [29], beta-alumina [30], Na 2 M 2 TeO 6 (M = Ni 2+ , Zn 2+ , Co 2+ , or Mg 2+ ) [31][32][33][34], Na 1+x Zr 2 Si x P 3−x O 12 [26], and some liquids [35], where it satisfactorily mimicked various experimental observations.…”
Section: Introductionmentioning
confidence: 54%
“…Na2 is sandwiched between the triangular faces of the ZnO 6 octahedra, and Na3 is between the ZnO 6 octahedra and TeO 6 octahedra. Based on a molecular dynamics (MD) simulation of Na + ion transport in Na 2 Ni 2 TeO 6 (NNTO), Na + ions migrate from Na1 to Na2, but with less contribution from Na3 because the potential energy of Na1 and Na2 (−2.45 and −2.65 eV, respectively) is much lower than that of Na3 (−2.32 eV) . However, our bond valence sum (BVS) studies show that Na3 has nearly equal potential energy to Na1 and Na2 in Na 2 Zn 2 TeO 6 (NZTO) (see Figure S1, Supporting Information) because the repulsion of Na + with Zn 2+ of NZTO is much less than that of Na + with Te 6+ of NNTO.…”
Section: Figurementioning
confidence: 91%